Screening for Acyanogenesis in cassava: IITA Technical Bulletin No 4 - Sadik, S.; Okereke, O.; Hahn, S. (1974)
The sodium picrate test for hydrocyanic acid was used (0 evaluate BB.S10cassava plants for cyanogenic content. Acyanogenic plants were not found in spite of the large number of plants rested. A small number of plants exhibited low to medium degree of cyanogenesis while the rest of [he plants showed a high degree of cyanogenesis. The screening method is simple and sensitive and lends itself to large •scale field screening.